2015
DOI: 10.1515/ijamh-2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of the perpetration of cyberbullying among in-school adolescents in Oyo State, Nigeria

Abstract: About a quarter of students were perpetrators of cyberbullying, and the correlates of perpetration were history of cyber victimization and daily Internet access. Intervention programs must be instituted for victims as well as frequent users of the Internet to curb the problem in the study area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 27 publications
(81 reference statements)
2
26
0
Order By: Relevance
“…This was much higher than phone ownership rates of about 40% in 2012 [15] .The higher mobile phone ownership rate reported in the current study might be reflection of the increasing access to mobile phones by adolescent and young persons in Nigeria. The proportion of young persons with internet access is comparable to findings by Olumide et al who reported that about half of the in-school adolescents they interviewed had access to the internet [16] . Other studies among young people in Nigeria have also reported that many of them own mobile phones [17] .…”
Section: Discussionsupporting
confidence: 83%
“…This was much higher than phone ownership rates of about 40% in 2012 [15] .The higher mobile phone ownership rate reported in the current study might be reflection of the increasing access to mobile phones by adolescent and young persons in Nigeria. The proportion of young persons with internet access is comparable to findings by Olumide et al who reported that about half of the in-school adolescents they interviewed had access to the internet [16] . Other studies among young people in Nigeria have also reported that many of them own mobile phones [17] .…”
Section: Discussionsupporting
confidence: 83%
“…12 In Nigeria, the prevalence of bullying ranges between 21% and 82%. [13][14][15][16][17][18][19][20][21] Awareness of bullying and associated health problems has increased globally. However, studies describing the burden of bullying in Africa is limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies describing the burden of bullying in Africa is limited. 22 This is the case in Nigeria where only a few studies [16][17][18][19][20][21]23 (mostly in the southern part of the country) have reported the prevalence, with none of these…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence is beginning to emerge that CBCV is a concern in developing nations as well (Badenhorst, 2011;Ephraim, 2013). For example, recent work from Nigeria found that over half of the secondary-school students sampled were aware of some sort of cyber aggression happening at their school or among their friends (Olumide et al, 2015) and that almost a quarter of adolescents had engaged in some sort of cyber perpetration (Olumide, Adams, & Amodu, 2016). Moreover, another study from Nigeria found that being cyberbullied was linked to lowered levels of self-esteem and self-concept (Okoiye, Anayochi, & Onah, 2015).…”
mentioning
confidence: 99%